COMIC STRIPS: A REFLECTION OF THE AMERICAN SPIRIT - Ekawati Marhaenny Dukut (Celt: A Journal of Culture, English Language Teaching & Literature, 2001)
Popular culture by definition includes customs, beliefs and practices, which is massed produced and shared by a society. It can include a best selling magazine, film, food or drink products. It is widely enjoyed by the society because of its cheap price and meets the consumer's needs. Comic strips, is one of those products. Reading comic strips is fun and enjoyable because it does not need full concentration or extra money as a way of passing time. It is massed produced cheaply in popular magazines, newspapers and films. Although it is a way of passing time, it is also a way of learning about the American history, politics, economy, society and spirit of honesty, freedom and the hope of a better future. The comic strip, to say briefly, is a reflection of the American spirit